MAINTAINING THE INFLUENCE OF POWERLESS SURAKARTA HADININGRAT KINGDOM OVER THE SUBJECTS TROUGH RITUAL (The symbolic meaning of Heir Procession On 1 st Muharram at Surakarta Hadiningrat Court) - Idrus Alkaff (JIA (Jurnal Ilmu Agama), 2016)
Surakarta  Sultanate  today  no  longer  has  the  administrative  power  in  Surakarta  and surrounding  communities.  Surakarta  Sultanate  has  lost  its  power  since  the  Dutch  colonial.  The dutch  intentionally  weaken  it.  It  position  subjected  to  the  Chief  Resident  of  Surakarta.  From independence until today, The power of sultanate is only to the extent of its palace buildings.Even so its existence is inherent in the heart of Surakarta people and surrounding areas. This paper will try  to  see  the  construction  of  meaning  the  symbol  of  ritual  Heir  Procession  held  each  night  1 Muharram  by  Kraton  Surakarta  Sultanate.  Through  functional  approach  of  culture  offered  by Geertz, that culture as a system of symbols which is the symbols of and the symbol for, this paper argues that this ritual contains various symbols of spirituality, values, ethics and also an effort to maintain the hierarchical power between the king's palace, nobles and the subjects in the cultural life of Surakarta and surrounding communities.